SARS-CoV-2 spike-protein D614G mutation increases virion spike density and infectivity - Zhang, Lizhou (Nat Commun, 2020)
SARS-CoV-2 variants with spike (S)-protein D614G mutations now predominate globally. We therefore compare the properties of the mutated S protein (S(G614)) with the original (S(D614)). We report here pseudoviruses carrying S(G614) enter ACE2-expressing cells more efficiently than those with S(D614). This increased entry correlates with less S1-domain shedding and higher S-protein incorporation into the virion. Similar results are obtained with virus-like particles produced with SARS-CoV-2 M, N, E, and S proteins. However, D614G does not alter S-protein binding to ACE2 or neutralization sensitivity of pseudoviruses. Thus, D614G may increase infectivity by assembling more functional S protein into the virion.